Integration of Molecular Factors Influencing VCAM-1 Expression in Vascular Inflammation and Atherosclerosis: A Narrative Review - Nur Asini; Taufik Indrajaya; Irfannuddin; Siti Sarahdeaz Fazzaura Putri (GoAcademica Research & Publishing, 2026)
Vascular Cell Adhesion Molecule-1 (VCAM-1) is a vascular adhesion molecule that plays a crucial role in vascular inflammation, endothelial dysfunction, and the development of atherosclerosis. Increased VCAM-1 expression occurs in response to various inflammatory stimuli and cellular stressors that involve the activation of specific molecular signaling pathways. Various factors such as chronic inflammation, oxidative stress, activation of the Nuclear Factor-kappa B (NF-κB) pathway, the Janus Kinase-Signal Transducer and Activator of Transcription (JAK-STAT) pathway, obesity, leptin resistance, genetic factors, and changes in vascular hemodynamics are known to contribute to increased VCAM-1 expression. This study aims to analyze various factors that influence VCAM-1 changes molecularly using a narrative review method. Article searches were conducted through the PubMed, Scopus, and Google Scholar databases using the keywords